Imaging of Pelvic and Femoral Fixation Hardware: Normal Findings and Hardware Failure - Sanal, Hatice Tuba; Boulton, Christina; Neyisci, Cagri; Erdem, Yusuf; Lowe, Jason (Seminars in Musculoskeletal Radiology, 2019)
Good outcomes following treatment of pelvic ring injuries, acetabular fractures, and femur fractures rely on restoration of native pelvic or limb alignment, anatomical reduction and rigid stability of articular fractures, and early postoperative mobilization. Multiple surgical approaches, reduction aids, and orthopaedic implants are available to stabilize these fractures. Despite best practices, complications including hardware failure, nonunions, malunions, and infections occur. This article discusses common fracture classification systems, implants, and imaging findings associated with unwanted complications in fractures of the pelvis, acetabulum, and femur.
Keywords: pelvis; acetabulum fracture; femur fracture; external fixation; internal fixation